Peningkatan Pemahaman Siswa tentang Konsep Bentuk bentuk Kerjasama dalam Organisasi pada Pelajaran PKn dengan Menerapkan Model Bermain Peran (Role Playing) - Tuti Awaliyah (LP. Ma'arif Janggan Magetan, 2023)
This study aims to determine the increase in students' understanding of the concept of forms of cooperation that exist in an organization. The reason for this class action research is that there are many students who have not graduated when the evaluation is carried out on the concept of forms of cooperation in organizations. After applying the role-playing model in Civics lessons about the concept of forms of cooperation in organizations in grade IV SDN Tegal Kalong, it turns out that students' understanding has increased.